Hybrid Descemet Membrane Endothelial Keratoplasty (H-DMEK): results of a donor insertion pull-through technique using donor stroma as carrier. Issue 10 (16th January 2020) - Woo, Jyh Haur; Htoon, Hla Myint; Tan, Donald
Abstract : Aim: To evaluate the outcomes and complications of hybrid Descemet membrane endothelial keratoplasty (H-DMEK) using a Descemet stripping automated endothelial keratoplasty (DSAEK) pull-through donor inserter and donor stroma as carrier. Methods: This was a retrospective interventional case series of eyes with bullous keratopathy (BK) and Fuchs endothelial corneal dystrophy (FECD), which underwent H-DMEK, performed using a bimanual pull-through technique using DSAEK-prepared donor stroma as carrier and the EndoGlide Ultrathin DSAEK donor insertion device. Complex cases with tube shunts, trabeculectomy, aphakia, aniridia, previous vitrectomy, keratoplasty or combined with intraocular lens exchange, were also included. The outcome measures were intraoperative and postoperative complications, best corrected visual acuity (BCVA) and endothelial cell loss after surgery. Results: Of the 85 eyes from 79 patients, 43.5% (n=37) had BK, 28.2% (n=24) had FECD while 24.7% (n=21) had failed grafts. DMEK was performed in 37 complex eyes (43.5%). Four eyes (4.7%) required rebubbling for graft detachment and two cases of graft failure were observed. A BCVA of 20/25 or better was attained in 44.7% and 57.1% of eyes without pre-existing ocular pathology at 6 and 12 months, respectively. The overall endothelial cell loss was 32.2%±20.5% at 6 months, which improved from 37.2%±20.9% to 24.2%±17.5%, comparing the first 40 and last 45 cases (p=0.012). Conclusion: Hybrid DMEK offers a controlled 'pull-through' technique of donor insertion in the 'endothelium-in' configuration, which may be useful especially in complicated eyes. More studies are needed to confirm the long-term endothelial cell loss and graft survival associated with this technique.